Analysis of the implementation of flood disaster management policy reviewed from law number 24 of 2007 concerning disaster management in Banten province - Rizki Amilia; Fitria Pertiwi; M. Nassir Agustiawan; Reza Damayanti (Institute Of computer Science (IOCS), 2026)
Banten Province is one of the regions with a high level of flood vulnerability due to rainfall, environmental damage, land conversion, and low public awareness of disaster mitigation. This study uses a qualitative research method with a normative and empirical juridical approach through literature studies, observations, and analysis of the implementation of local government policies in flood disaster management. The results show that the implementation of disaster management policies in Banten Province has referred to the principles stipulated in Law Number 24 of 2007, covering the pre-disaster, emergency response, and post-disaster stages. However, policy implementation still faces various obstacles, such as limited facilities and infrastructure, poor coordination between agencies, minimal disaster education for the community, and weak supervision of regional spatial planning. In addition, community participation in disaster mitigation and preparedness is still not optimal. The local government through the Regional Disaster Management Agency (BPBD) has made various efforts, such as compiling disaster hazard maps, mitigation outreach, and emergency response during floods, but their effectiveness still needs to be improved. This study concludes that the successful implementation of flood disaster management policies in Banten Province requires synergy between the government, the community, and other stakeholders to create an effective, integrated, and sustainable disaster management system in accordance with the mandate of laws and regulations.